2016
DOI: 10.1088/1674-1056/25/4/047503
|View full text |Cite
|
Sign up to set email alerts
|

Study of magnetization reversal and anisotropy of single crystalline ultrathin Fe/MgO (001) film by magneto-optic Kerr effect

Abstract: The magnetization reversal process of Fe/MgO (001) thin film is investigated by combining transverse and longitudinal hysteresis loops. Owing to the competition between domain wall pinning energy and weak uniaxial magnetic anisotropy,the typical magnetization reversal process of Fe ultrathin film can take place via either an "l-jump" process near the easy axis, or a "2-jump" process near the hard axis, depending on the applied field orientation. Besides, the hysteresis loop presents strong asymmetry resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…5(c) ) the sudden increase of the MOKE intensity than the positive saturation one indicates presence of transverse component in the sample. As discussed earlier, this asymmetry (sudden increase) in the hysteresis loop arises due to the dominance of quadratic component of MOKE over the linear one 39 43 . It should be noted that the asymmetry present in the loop along ϕ = 45° (Fig.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…5(c) ) the sudden increase of the MOKE intensity than the positive saturation one indicates presence of transverse component in the sample. As discussed earlier, this asymmetry (sudden increase) in the hysteresis loop arises due to the dominance of quadratic component of MOKE over the linear one 39 43 . It should be noted that the asymmetry present in the loop along ϕ = 45° (Fig.…”
Section: Resultsmentioning
confidence: 68%
“…It has been reported in previous literature that this asymmetry in hysteresis loops in Fe samples occurs due to the quadratic component of the MOKE. Near the hard axis of the sample the quadratic component becomes dominant over the linear one of the MOKE which gives rise to sudden jumps in hysteresis loops 39 43 . Further in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Different to the longitudinal Kerr signal that is characteristic of the light intensity related to the M component variation along the H direction, the transverse Kerr reflects the light intensity variation perpendicular to the H direction. Since the transverse M component is close to zero at positive or negative saturated H [28], the Kerr signal intensity and the magnetic domain image contrast are almost equal in figures 4(c) and (d) (state 1 and 6). Similarly, during increasing H from −101.6 Oe to 101.6 Oe, M first rotates coherently to be orientated with the easy axis [010] direction (stage 2).…”
Section: Resultsmentioning
confidence: 91%
“…There is also a noticeable 6th order contribution Hk 6 ( Table 4 ) along with the cubic Hk 4 (4th order) symmetry axis [ 52 , 55 , 56 ]. For example, for lines presented on Figure 12 b we found that Hk 6 is greater than Hk 4 .…”
Section: Resultsmentioning
confidence: 99%